PENGARUH PENGHARGAAN DAN HUKUMAN TERHADAP MOTIVASI YANG BERDAPAK KEPADA KINERJA PENYALURAN KREDIT USAHA RAKYAT (KUR) MIKRO PADA PT. BANK RAKYAT INDONESIA (PERSERO) Tbk KANTOR CABANG PURWAKARTA - Indra Herwinda (BUANA ILMU, 2018)
ABSTRAK This research aim to know influence of reward (X1), punishment (X2), to motivation (Y) and work performance (Z). Population of this researchare all mantri at PT. Bank Rakyat Indonesia (Persero). Tbk Plant Office Purwakarta. 120 of mantri and sampel a number of 55 mantri. This research is including explanatory research. Analytical technique applied by pathanalysis. Independen variable in this research are reward and punishment, dependent variable is motivation and output variable is work performance. Based on result of research with hypothesis test obtained information that reward variable (X1) has significant effect to motivation (Y) with value Î² = 0,308. And Ï â€“ value= 0,05, punishment variable (X2) not has significant effect to motivation (Y) because value Î²= 0,035 and Ï â€“ value = 0,82. Motivation variable (Y) has significant effect to work performance (Z) with value Î² = 0,370 and Ï â€“ value = 0,01. Based on result of analysed hence can be concluded that reward (X1) have significant effect to motivation ( Y) that impact to performance ( Z). Key word: Reward, Punishment, Motivation and Work Performance